Road safety survey 1994 - Swedish Road Administration (Swedish Transport Administration, 2013)
This is the 14th study in a series of annual surveys on road safety conducted since 1981. The study is conducted by Statistics Sweden on behalf of the Swedish National Road Administration, which had the overall responsibility for road safety in Sweden in 1994. Today the study is conducted on behalf of the Swedish Transport Administration.

The study aims to identify and analyse traffic safety statistics. This is done by a written questionnaire directed to a stratified sample of the population. The study from 1994 had a 79.4 percent response rate and a sample of 5 985 randomly selected people aged between 15 and 74 years.

The questions in the study include, for example, traffic behaviour and traffic patterns; attitudes to road safety and traffic rules, the relation between alcohol and traffic and child safety in traffic. Both motor traffic, bicycle and foot traffic is concerned. A total of 31 questions are used, including descriptive questions, estimation questions and attitude questions.
.

Purpose:

The survey aims to identify and analyse traffic safety statistics.

Detta är den fjortonde studien i en serie av årliga undersökningar om trafiksäkerhet, som genomförts sedan 1981. Studien har utförts av Statistiska centralbyrån på uppdrag av Vägverket, som 1994 hade det övergripande ansvaret för trafiksäkerheten i Sverige. Idag utförs studien på uppdrag av Trafikverket.

Undersökningen syftar till att ta fram och analysera trafiksäkerhetsstatistik. Detta görs med en skriftlig enkät riktad till ett stratifierat urval av Sveriges befolkning. För studien 1994 var svarsfrekvensen 79,4 procent och urvalet 5985 slumpmässigt utvalda personer i åldrarna 15 till 74 år.

Frågorna i studien behandlar bland annat trafikbeteende och trafikvanor, både hos sig själv och andra, inställning till trafiksäkerhet och trafikregler, relationen mellan alkohol och trafik samt barns säkerhet i trafiken. Både motortrafik, cykel och gångtrafik berörs. Totalt används 31 stycken frågor som består bland annat av beskrivande frågor, skattningsfrågor och attitydfrågor.

Syfte:

Syftet med studien är att ta fram och analysera trafiksäkerhetsstatistik.
Trafiksäkerhetsenkäten 1994
TS-enkäten 1994
Keywords: drinking behaviour; alkoholvanor; road traffic; vägtrafik; speed limits; fartgräns; protective headwear; skyddshjälmar; road accidents; trafikolyckor; road safety; trafiksäkerhet; child safety; barnsäkerhet; traffic regulations; trafikbestämmelse; accidents; olyckor; traffic; trafik; road users; vägtrafikanter; velocity; hastighet; vehicle restraint systems; bilens inre säkerhet; traffic offences; trafikförseelse; Wounds and injuries; Sår och skador; Legislation and legal systems; Lagstiftning och rättssystem; Children; Barn; TRANSPORT AND TRAVEL; TRANSPORT OCH RESOR; Social Sciences; Samhällsvetenskap